Letrando cientificamente alunos da educação básica por meio da pesquisa sociolinguística em sala de aula - Oliveira, Ana Lúcia Alves de (2021)
This research aims to develop a didactic proposal for students in the Final Years of Elementary School (ES), with the aim of contributing to improving the teaching of grammatical contents from a variationist perspective, through scientific literacy. As Portuguese language teachers, we observe that students reach the final years of ES with superficial knowledge of linguistic variation, because they associate popular linguistic varieties with “errors” or stereotyped examples. On the other hand, we believe in PL didactic proposals aimed at training people who are critical and knowledgeable about their reality, capable of communicating in the various situations in which they are socially inserted. Based on that, we were motivate to choice of the theme for this research: taking sociolinguistic research into the classroom of Basic Education, with a view to training student researchers in their own language. We believe scientific literacy (SILVA, W. 2016; CUNHA, 2017, SASSERON; CARVALHO, 2011) is an essential factor for the training of student researchers, since the practice of research in the classroom is almost nil and, when carried out, sometimes the students are not taught how to adequately develop a particular research. In order to elaborate such a proposal, we will rely on the studies of Educational Sociolinguistics (BORTONI RICARDO, 2004, 2005, 2013) with a view to activities that explore some prescriptions of Normative Grammar, but also the rules of linguistic variation, based on in the description and analysis of the language in use, according to the theoretical methodological model of Variationist Sociolinguistics (LABOV, [1972] 2008), in order to propose a didactic transposition of this model to the students' reality, thus conducting a sociolinguistic research in Basic Education. We emphasize that this PL teaching model that respects the linguistic diversity of Brazilians is encouraged in normative documents, such as the Common National Curriculum Base (BRASIL, 2018)